Strategic Power Flow-Stackelberg Dynamics for Minimizing Transmission Losses in Peer-to-Peer Trading - K. V. Biji Varghese; Dattatraya N. Gaonkar (IEEE Access)
This article presents a new decentralized game-theoretic method for peer-to-peer energy trading in a networked microgrid distribution system, incorporating transmission losses. In networked microgrids, some units may have surplus energy while others experience deficits, creating a buyer-seller trade dynamic. This dynamic is modeled using a multi-leader, multi-follower Stackelberg game. Seller microgrids initiate the game by proposing trading prices that account for transmission losses and the amount of energy to be traded, while the buyer microgrids respond by optimizing their trading strategies based on these proposed prices. The study develops distributed algorithms to achieve Stackelberg equilibrium, ensuring fair and efficient energy trading, and addresses privacy concerns among microgrids as well. The effectiveness of the proposed approach is evaluated on two test systems: a 6-microgrid setup and the IEEE 9-bus system, assessing its performance in practical scenarios. Additionally, the scalability and robustness of the proposed approach are tested on the larger and more complex IEEE 33-bus system. Results from these tests are compared with existing energy trading systems, highlighting improvements in scalability, efficiency, and overall performance. This comparative analysis provides insights into the advantages of decentralized game-theoretic mechanisms in enhancing the management of peer-to-peer energy transactions within extensive microgrid networks, while also reducing power losses.